Debris Management - Sakai, Shinichi (World Bank, Washington, DC, 2013)
Some 20 million tons of waste resulted from the Great East Japan Earthquake (GEJE). The amount of debris in Iwate prefecture was 11 times greater than in a normal year, and in Miyagi 19 times greater. Appropriate treatment and disposal depends on the type of debris or waste, while recycling should also be considered. Authorities should prepare for disasters by designating temporary storage sites and routes for transporting waste. Japan's existing debris management plans are being revised to include methods for estimating the amount of disaster waste generated by tsunamis and appropriate measures for dealing with it. This report gives findings; lessons; and recommendations for developing countries.